2016
DOI: 10.1007/s00285-016-1026-0
|View full text |Cite
|
Sign up to set email alerts
|

A numerical scheme for the early steps of nucleation-aggregation models

Abstract: In the formation of large clusters out of small particles, the initializing step is called the nucleation, and consists in the spontaneous reaction of agents which aggregate into small and stable polymers called nuclei. After this early step, the polymers are involved in a number of reactions such as polymerization, fragmentation and coalescence. Since there may be several orders of magnitude between the size of a particle and the size of an aggregate, building efficient numerical schemes to capture accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In [52] and subsequent efforts in [12,13], the authors sought to investigate several questions including (i) understanding the key polymerization mechanisms, (ii) numerical approximation of the models, and (iii) selection of parameters and calibration of the model. Here we focus on illustrating the methodology used in (iii).…”
Section: Prions and Protein Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In [52] and subsequent efforts in [12,13], the authors sought to investigate several questions including (i) understanding the key polymerization mechanisms, (ii) numerical approximation of the models, and (iii) selection of parameters and calibration of the model. Here we focus on illustrating the methodology used in (iii).…”
Section: Prions and Protein Polymerizationmentioning
confidence: 99%
“…Following [12,53], we define a small parameter ε = 1 i M , and let x i = iε with i M 1 being the average polymer size defined by…”
Section: A Hybrid Ode/pde Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed methodology for forward solutions in [7]. In considering these forward solutions we first observed that the desired spatial computational domain is very large as determined by the maximum size of observed polymers, with range up to 10 6 and the peak in the distribution is at the left side of the domain of interest; for larger polymer sizes, the distribution is almost linearly decreasing.…”
Section: An Approximate Pde System and The Associated Forward Problemmentioning
confidence: 99%
“…Note that there are many other possible applications of this model, such as phase transition, which was the original application for which it had been designed [14]. The problem now stands: Measuring z sls (t) or z tht (t), or more generally the timedependence of a n-th moment defined by 0 x n u(x, t)dx, with u(x, t) solution of System (1) (2), what may be possibly estimated among the unknown quantities, i.e. the initial state u 0 (x) and the parameter functions a(x) and b(x)?…”
Section: Introductionmentioning
confidence: 99%